Identification of New miRNA-mRNA Networks in the Development of Non-syndromic Cleft Lip With or Without Cleft Palate - Fu, Chengyi; Lou, Shu; Zhu, Guirong; Fan, Liwen; Yu, Xin; Zhu, Weihao; Ma, Lan; Wang, Lin; Pan, Yongchu (Frontiers in Cell and Developmental Biology, 2021)
Objective: To identify new microRNA (miRNA)-mRNA networks in non-syndromic cleft lip with or without cleft palate (NSCL/P). Materials and methods: Overlapping differentially expressed miRNAs (DEMs) were selected from cleft palate patients (GSE47939) and murine embryonic orofacial tissues (GSE20880). Next, the target genes of DEMs were predicted by Targetscan, miRDB, and FUNRICH, and further filtered through differentially expressed genes (DEGs) from NSCL/P patients and controls (GSE42589), MGI, MalaCards, and DECIPHER databases. The results were then confirmed by in vitro experiments. NSCL/P lip tissues were obtained to explore the expression of miRNAs and their target genes. Results: Let-7c-5p and miR-193a-3p were identified as DEMs, and their overexpression inhibited cell proliferation and promoted cell apoptosis. PIGA and TGFB2 were confirmed as targets of let-7c-5p and miR-193a-3p, respectively, and were involved in craniofacial development in mice. Negative correlation between miRNA and mRNA expression was detected in the NSCL/P lip tissues. They were also associated with the occurrence of NSCL/P based on the MGI, MalaCards, and DECIPHER databases. Conclusions: Let-7c-5p-PIGA and miR-193a-3p-TGFB2 networks may be involved in the development of NSCL/P.